The politics of climate denialism and the secondary denialism of economics. - Cobb, Clifford William (American Journal of Economics & Sociology, 2025)
Primary climate‐change denialism rejects the idea that global warming is driven by human activity. This belief system now appeals to about one‐third of Americans. Having been influenced by a 1990s Exxon campaign to sow doubt that fossil fuels are responsible for global warming, Republicans are more likely than Democrats to be primary climate‐change deniers. But polls show that many US climate‐change accepters do not take it seriously enough to pay a nominal sum to prevent continued warming. This secondary denialism (accept the science, deny the urgency of action) may stem from the economic analysis of climate change. Discounting future damage and believing that economic growth will compensate for damage are two standard features of economic theory that justify treating climate issues with a degree of apathy—or at least as low priority. The work of Nobel‐Prize‐winning economist William Nordhaus provides almost as much cause for indifference among accepters as the climate denialists offer their followers. Scientists may view climate change with alarm, but policy‐makers mostly take their cues from economists. Nordhaus stated in a popular book in 2008 that his model demonstrates that 3.45°C warming is economically optimal. Not just tolerable, but optimal. His work is highly influential. Even though some economists have objected to the methods of economic analysis that understate the perils of climate change, their voices have had little influence on policy. Thus, seeming partisan differences about climate change have converged around go‐slow polices that manage climate issues as technical problems and that do not impose significant demands upon citizens or disrupt present economic arrangements.